Analisis Pengaruh Kelembagaan Kelompok Tani terhadap Produksi Gula Kelapa di Kecamatan Cilongok Kabupaten Banyumas - Aulia, Wina Taskia; Istiqomah, Istiqomah; Barokatuminalloh, Barokatuminalloh (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
Banyumas Regency has one of the leading commodities, namely coconut plantations. One of the sub-districts in Banyumas Regency which is the center of the coconut sugar industry is Cilongok District. This is indicated by the higher production numbers compared to other regions. The coconut sugar industry is able to absorb a lot of workers. However, the production volume of each craftsman varies. Meanwhile, craftsmen make their daily living by producing coconut sugar. Therefore, it is necessary to carry out research with the title